Biomass‐Derived Hierarchically Porous (Nitrogen, Phosphorus) Co‐Doped SiOx/C Composite Nanosheet Architectures for Superior Lithium Storage and Ultra‐Long Cycle Performance. Issue 4 (9th February 2022) - Song, Luting; Zhao, Tingqiao; Tan, Xinghua; Mao, Dongdong; Su, Sai; Fan, Zhengwei; Chu, Weiguo
Abstract: Biomasses receive much attention as carbon sources for anodes of high‐energy lithium‐ion batteries and cathodes of lithium‐sulfur batteries due to their low costs, easy availability and potentially high capacities which unfortunately deliver unsatisfactory performances normally. However, biomasses used as silicon instead of carbon‐dominated sources have never been touched before. Here, we report a facile preparation of nitrogen and phosphorus heteroatoms co‐doped hierarchically porous and cross‐linked SiO x /C composite nanosheet architectures from catkins without the introduction of alien Si (N/P‐SiO x /C‐NSs) using chemical exfoliation and treatments. This unique structure composed of novel multiple‐phase composites is revealed to show superior fast kinetics and ultra‐long cycle life with about 340 mAh g −1 and almost no capacity decay after 10000 cycles at 10 A g −1, far beyond those of conventional carbon and SiO x ‐based anode materials. The superior performance is closely related to excellent electronic conduction arising from the cross‐linkage architecture, well‐graphitized carbon and uniform co‐doping of nitrogen and phosphorus, rapid ionic transport kinetics from rich hierarchical pores, and outstanding stability from the rigid nanosheet networks. This study sets a precedent of catkins as silicon instead of conventional carbon‐only sources for anode materials, which can largely enhance the role of biomasses in energy storage. Abstract : Biomass SiO x ‐based anode materials : We utilize catkins to achieve nitrogen and phosphorus heteroatoms co‐doped hierarchically porous and cross‐linked SiO x /C composite nanosheet architectures without the introduction of alien Si (N/P‐SiO x /C‐NSs) by chemical exfoliation and treatments. This as‐prepared N/P‐SiO x /C‐NSs is revealed to show superior fast kinetics and ultra‐long cycle life with about 340 mAh g −1 and almost no capacity decay after 10000 cycles at 10 A g −1 .